Strengthening Reintegration through Social Capital: Learning from Aceh, Indonesia - Nirzalin, Nirzalin; Bachri, Naufal; Fakhrurrazi, Fakhrurrazi; Yunanda, Rizki; Ilham, Iromi; Muchlis, Muchlis (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
Following the conflict that prevailed from 1976 to 2005, a state of social disintegration persisted between former combatants of the Gerakan Aceh Merdeka - GAM (Free Aceh Movement) and the civil society in Aceh. This disintegration was typically fueled by the former GAM combatants’ militaristic and pragmatic mindsets, instability, and low economic well-being. Interestingly, former GAM combatants in Nisam Antara Subdistrict, North Aceh Regency, have managed to collaborate and coexist with local communities, exemplifying successful social reintegration that distinguishes them from their counterparts in other regions of Aceh. This article delves into the reality of social reintegration between former GAM combatants and the local populace, with a specific focus on the oil palm plantations managed by former GAM combatants. The study adopts a descriptive qualitative approach, and data was gathered through a combination of observations, in-depth interviews, document analyses, and focus group discussions. Key informants for this study included former GAM combatants, community and traditional leaders, plantation workers, and members of civil society. The study reveals that moral obligations within communities are guided by local wisdom, which acts as a form of social capital that fosters economic and social collaborations. Local wisdom serves as a social capital that nurtures the development of fraternity, mutual trust, cooperation, and solidarity. Moreover, it has the capacity to minimize differences and resentments, thereby promoting unity between former GAM combatants and local communities. This unity significantly contributes to the sustainability of peace in Aceh, Indonesia.